2013
DOI: 10.3390/ijms14012085
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment of Platinum Resistant Ovarian Cancer Cells with an MMP-9/MMP-2 Inhibitor Prior to Cisplatin Enhances Cytotoxicity as Determined by High Content Screening

Abstract: Platinum resistance is a major cause of treatment failure in ovarian cancer. We previously identified matrix metalloproteinase 9 (MMP-9) as a potential therapeutic target of chemoresistant disease. A2780cis (cisplatin-resistant) and A2780 (cisplatin-sensitive) ovarian carcinoma cell lines were used. The cytotoxic effect of MMP-9/MMP-2 inhibitor, (2R)-2-[(4-Biphenylsulfonyl) amino]-3 phenylpropionic acid (C21H19NO4S) alone or in combination with cisplatin was determined using high content screening. Protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Multiple downstream TWIST1 target genes have been implicated in drug resistance, including interleukin 8 and matrix metalloproteinases 2 and 9141516. Additionally, TWIST1 has been shown to regulate Gli1, which upregulates the DNA repair protein ERCC1.…”
mentioning
confidence: 99%
“…Multiple downstream TWIST1 target genes have been implicated in drug resistance, including interleukin 8 and matrix metalloproteinases 2 and 9141516. Additionally, TWIST1 has been shown to regulate Gli1, which upregulates the DNA repair protein ERCC1.…”
mentioning
confidence: 99%
“…As another example MMP2, a member of the matrix metalloproteinase family involved in the breakdown of the extracellular matrix, was ranked 9 using ProGENI, while Pearson correlation analysis did not place it among the top 15. An inhibitor of MMP2 has been shown to significantly increase cytotoxicity in cisplatin resistant ovarian carcinoma cell line, A2780cis [30]. In addition to the 9 (of 15) genes with direct literature evidence, our own experiments revealed that knockdown of three of the remaining 6 predicted genes, TUBB6, DYNC2H1, and ELK3, significantly sensitized both cell lines to cisplatin treatment ( Fig.…”
Section: Functional Validations Confirm the Role Of Progeni-identifiementioning
confidence: 68%
“…These figures are drawn using Cytoscape [89]. shown to significantly increase cytotoxicity in cisplatin resistant ovarian carcinoma cell line, A2780cis [30]. In addition to the 9 (of 15) genes with direct literature evidence, our own experiments revealed that knockdown of three of the remaining 6 predicted genes, TUBB6, DYNC2H1, and ELK3, significantly sensitized both cell lines to cisplatin treatment (Fig.…”
Section: Functional Validations Confirm the Role Of Progeni-identifiementioning
confidence: 78%
“…MMPs are proteolytic enzymes, which have the potential capacity of degrading the extracellular matrix (ECM) components (28). In particular, MMP-2 and MMP-9 disintegrate type-IV collagen, which is the main component of the basement membrane (29). A study has demonstrated a marked increase in MMP-2 and MMP-9 levels in the ADS tissue (3).…”
Section: Discussionmentioning
confidence: 99%